1994
DOI: 10.1128/jb.176.8.2326-2338.1994
|View full text |Cite
|
Sign up to set email alerts
|

Role of the TonB amino terminus in energy transduction between membranes

Abstract: Escherichia coli TonB protein is an energy transducer, coupling cytoplasmic membrane energy to active transport of vitamin B12 and iron-siderophores across the outer membrane. TonB is anchored in the cytoplasmic membrane by its hydrophobic amino terminus, with the remainder occupying the periplasmic space. In this report we establish several functions for the hydrophobic amino terminus of TonB TonB protein is anchored in the cytoplasmic membrane by its uncleaved amino terminus, with the bulk of the protein occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 47 publications
6
86
1
Order By: Relevance
“…We have previously shown that TetA-TonB protein can be cross-linked to the outer membrane receptor FepA (Jaskula et al, 1994). Consistent with those observations, TetA-TonB was found to be associated with the outer membrane in sucrose density gradients.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…We have previously shown that TetA-TonB protein can be cross-linked to the outer membrane receptor FepA (Jaskula et al, 1994). Consistent with those observations, TetA-TonB was found to be associated with the outer membrane in sucrose density gradients.…”
Section: Discussionsupporting
confidence: 82%
“…Previous observations suggested that the latter is unlikely. First, TetA-TonB, which lacks the native TonB signal anchor, could associate with the outer membrane, and, as demonstrated previously, can be cross-linked to FepA (Jaskula et al, 1994) even though it is completely inactive, presumably due to the lack of its connection to the pmf. Second, DNP has no effect on the ability of TonB to cross-link to FepA in vivo (K. Postle and J. T. Skare, unpublished).…”
Section: Tonb Localizes With Both the Cytoplasmic And Outer Membranesmentioning
confidence: 72%
See 3 more Smart Citations